The effect of moderate-intensity acute aerobic exercise duration on the percentage of circulating CD31+ cells in lymphocyte population (Medical Journal of Indonesia, 2016)
Background: The increasing number of circulating CD31+ endothelial progenitor cells is one of the important factors for maintaining vascular homeostasis. Exercise will effectively increase the number of circulating CD31+ endothelial progenitor cells. This study aims to determine the effect of moderate-intensity acute aerobic exercise duration on the percentage of circulating CD31+ cells in untrained healthy young adult subjects. Methods: This study was an experimental study. Untrained healthy volunteers (n=20) performed ergocycle at moderate-intensity (64–74% maximum heart rate) for 10 minutes or 30 minutes. Immediately before and 10 minutes after exercise, venous blood samples were drawn. The percentage of CD31+ cells in peripheral blood was analyzed using flow cytometry. Data was statistically analyzed using student t-test. Results: There were no significant differences in the mean percentage of circulating CD31+ cells before and after exercise for 10 minutes and 30 minutes (p>0.05). However, there was a different trend in the percentage of circulating CD31+ cells after exercise for 10 minutes and 30 minutes. In the 10 minutes duration, 50% of subjects showed increase. Whereas in the 30 minutes duration, 80% of subjects showed increase. Conclusion: The percentage of circulating CD31+ cells before and after exercise for 10 minutes was not different compared to 30 minutes. However, data analysis shows that majority of subjects (80%) had increased in the percentage of circulating CD31+ cells after 30 minutes exercise.